Plasma activated water pre-treatment substantially enhances phage activity against Proteus mirabilis biofilms - Akash Shambharkar; Thomas P. Thompson; Laura A. McClenaghan; Paula Bourke; Brendan F. Gilmore; Timofey Skvortsov (Biofilm)
The ongoing antimicrobial resistance crisis has incentivised research into alternative antibacterial and antibiofilm agents. One of them is plasma-activated water (PAW), which is produced by exposing water to a cold plasma discharge. This process generates a diverse array of reactive oxygen and nitrogen species (ROS/RNS) with antimicrobial properties. Another intensively studied class of alternative antimicrobials are bacteriophages, attracting attention due to their specificity and strong antibacterial activity. As combinations of different types of antimicrobials are known to often exhibit synergistic interactions, in this study we investigated the combined use of cold atmospheric-pressure plasma-activated water and the bacteriophage vB_PmiS_PM-CJR against Proteus mirabilis biofilms as a potential option for treatment of catheter-associated urinary tract infections (CAUTIs).We compared the effect of two cold plasma discharge setups for PAW production on its antimicrobial efficacy against P. mirabilis planktonic and biofilm cultures. Next, we assessed the stability of the phage vB_PmiS_PM-CJR in PAW. Finally, we tested the antimicrobial activity of the phages and PAW against biofilms, both individually and in combinations.Our findings demonstrate that the combination of PAW with phage is more effective against biofilms compared to individual treatments, being able to reduce the number of biofilm-embedded cells by approximately 4 log. We were also able to show that the order of treatment plays an important role in the anti-biofilm activity of the phage-PAW combination, as the exposure of the biofilm to PAW prior to phage administration results in a stronger effect than the reverse order.This research underlines PAW's ability to potentiate phage activity, showcasing a considerable reduction in biofilm viability and biomass. Additionally, it contributes to the growing body of evidence supporting the use of phage-based combinatorial treatments. Overall, this sequential treatment strategy demonstrates the potential of leveraging multiple approaches to address the mounting challenge of antibiotic resistance and offers a promising avenue for enhancing the efficacy of CAUTI management.